When Government Subsidizes Its Own: Collective Bargaining Laws as Agents of Political Mobilization. Issue 4 (17th February 2015) - Flavin, Patrick; Hartney, Michael T.
<x xml:space="preserve">Abstract</x> Government policies can activate a political constituency not only by providing material resources to, or altering the interpretive experiences of, individual citizens, but also by directly subsidizing established interest groups. We argue that state laws mandating collective bargaining for public employees provided organizational subsidies to public sector labor unions that lowered the costs of mobilizing their members to political action. Exploiting variation in the timing of laws across the states and using data on the political participation of public school teachers from 1956 to 2004, we find that the enactment of a mandatory bargaining law significantly boosted subsequent political participation among teachers. We also identify increased contact from organized groups seeking to mobilize teachers as a likely mechanism that explains this finding. These results have important implications for the current debate over collective bargaining rights and for our understanding of policy feedback, political parties and interest groups, and the bureaucracy.